Cadmium aggravates the blood-brain barrier disruption via inhibition of the Wnt7A/β-catenin signaling axis. (1st May 2023) - Li, Chen-Xi; Talukder, Milton; Xu, Ya-Ru; Zhu, Shi-Yong; Zhao, Ying-Xin; Li, Jin-Long
Abstract: Cadmium (Cd) is a non-biodegradable widespread environmental pollutant, which can cross the blood-brain barrier (BBB) and cause cerebral toxicity. However, the effect of Cd on the BBB is still unclear. In this study, a total of 80 (1-day-old) Hy-Line white variety chicks (20 chickens/group) were selected and randomly divided into four (4) groups: the control group (Con group) (fed with a basic diet, n = 20), the Cd 35 group (basic diet with 35 mg/kg CdCl2, n = 20), the Cd 70 group (basic diet with 70 mg/kg CdCl2, n = 20) and the Cd 140 group (basic diet with 140 mg/kg CdCl2, n = 20), and fed for 90 days. The pathological changes, factors associated with the BBB, oxidation level and the levels of Wingless-type MMTV integration site family, member 7 A (Wnt7A)/Wnt receptor Frizzled 4 (FZD4)/β-catenin signaling axis-related proteins in brain tissue were detected. Cd exposure induced capillary damage and neuronal swelling, degeneration and loss of neurons. Gene Set Enrichment Analysis (GSEA) showed the weakened Wnt/β-catenin signaling axis. The protein expression of the Wnt7A, FZD4, and β-catenin was decreased by Cd expusure. Inflammation generation and BBB dysfunction were induced by Cd, as manifested by impaired tight junctions (TJs) and adherens junctions (AJs) formation. These findings underscore that Cd induced BBB dysfunction via disturbing Wnt7A/FZD4/β-catenin signaling axis. Graphical abstract: The study aims to reveal the mechanism of how cadmium (Cd) enters the brain and causes damage. This research demonstrated that cerebral tissue exposed to various Cd concentrations displayed capillary damage characterized by basement membrane disruption, tight junctions (TJs) damage, and markedly swollen astrocyte end feet. The finding highlights the Wnt7A/FZD4/β-catenin signaling axis, by which Cd induced blood-brain barrier (BBB) disruption. Image 1 Highlights: Cadmium induced blood-brain barrier disruption. Cadmium impaired formation of tight junctions and adherens junctions. Cadmium inhibited of the Wnt7A/β-catenin signaling axis.